2020
DOI: 10.1017/cjn.2020.32
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic Nucleus Stimulation in Pediatric Isolated Dystonia: A 10-Year Follow-up

Abstract: ABSTRACT:Objective:To evaluate the short-term and long-term clinical effectiveness and safety of subthalamic nucleus deep brain stimulation (STN-DBS) for medically intractable pediatric isolated dystonia.Methods:Using a longitudinal retrospective design, we assessed the clinical outcomes of nine patients who underwent STN-DBS for treatment-refractory pediatric isolated dystonia one decade ago (mean age at surgery: 15.9 ± 4.5 years). The primary clinical outcome used was assessed by retrospective video analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Shorter disease duration correlated positively with larger DBS treatment efficacy, with a more persistent improvement and larger treatment potential with STN stimulation. Similar experience has been described by others [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. STN DBS has also been successfully used in the management of Meige syndrome with motor score improvements in the range of 42.1-74% [54][55][56][57] and in tardive dystonia with improvements of 88-100% at up to 12-year follow-up periods [41,58,59].…”
Section: Discussionsupporting
confidence: 64%
“…Shorter disease duration correlated positively with larger DBS treatment efficacy, with a more persistent improvement and larger treatment potential with STN stimulation. Similar experience has been described by others [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. STN DBS has also been successfully used in the management of Meige syndrome with motor score improvements in the range of 42.1-74% [54][55][56][57] and in tardive dystonia with improvements of 88-100% at up to 12-year follow-up periods [41,58,59].…”
Section: Discussionsupporting
confidence: 64%
“…There is no data directly comparing GPi versus subthalamic nucleus (STN) or thalamic stimulation in the pediatric population. STN stimulation demonstrated good outcomes in one pediatric study of 9 patients with isolated dystonia [35]. A phase 1 trial exploring bilateral thalamic DBS targeting the nucleus ventralis intermedius/ ventral oral posterior (Vim/Vop) in pediatric patients with acquired dystonia showed outcomes comparable to pallidal stimulation [64].…”
Section: Surgical Considerations In Pediatric Dbsmentioning
confidence: 99%
“…DBS is associated with a significant decrease in medication requirements and sometimes in complete elimination of dystonia medications [21]. Limited series have reported long-term benefits in pediatric cohorts, at 10 years and beyond [35, 73].…”
Section: Long-term Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…A dual-target, crossover sham-controlled study has directly compared the clinical effects of GPi and STN stimulations in patients with dystonia, which indicated that the STN was a more effective target for dystonia than the GPi (17). STN-DBS is believed to improve the repetitive motions, abnormal posture, and quality of life of refractory patients with isolated dystonia (12,13,15,(18)(19)(20)(21). The motor outcomes of STN-DBS in the treatment of dystonia have been extensively studied (12)(13)(14)(15)(16)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%